Konsep Shifa’ dalam Alquran (Perspektif M. Quraish Shihab dalam Tafsir Al-Mishbah) - Fauzi Fathur Rozi; Syaiful Arif (Medan Resource Center, 2023)
This article aims to explore the concept of Shifa' (healing) in the Qur'an from the perspective of M. Quraish Shihab in his Tafsir Al-Misbah. The research adopts a qualitative approach with a focus on library research. The primary data sources are books directly related to the research topic. In Surah At-Taubah, verse 14, M. Quraish Shihab explains that Allah SWT relieves the hearts of the polytheists and removes the hidden anger that believers carry due to past persecutions. Surah Ash-Shu'ara', verse 80, emphasizes that healing can only be achieved through Allah SWT, particularly for those who deny His oneness. In Surah Al-Isra', verse 82, M. Quraish Shihab highlights the Qur'an as a remedy for doubts and spiritual ailments, serving as a source of mercy for believers. Furthermore, in Surah An-Nahl, verse 69, the commentary by Quraish Shihab in Fihi Shifa' linnasl explains the Qur'an's healing properties, often symbolized by honey, which is believed to possess medicinal qualities. Lastly, in Tafsir Al-Misbah, Surah Fushilat, verse 44, guidance and healing are interpreted as impacting individuals differently, with some benefiting and others remaining unaffected based on their beliefs.